Uterine Cancer Treatment: Experience in Two Centers in Nepal - Shrestha, Isha; Aryal, Binod; Karmacharya, Saujanya; Chitrakar, Neer Shobha; Joshi, Arun Prasad; Maharjan, Rima; Maharjan, Pabitra; Neupane, Samir; Koirala, Srijana; Pokharel, Pratit; et al. (Journal of Karnali Academy of Health Sciences, 2021)
Background: Information and studies regarding uterine cancer are limited in Nepal. The aim of this study is to assess the clinical characteristic features and treatment outcomes of uterine cancer managed in two hospitals of Nepal. Methods: A retrospective descriptive study was conducted of all uterine cancer cases managed in gynecology department of Civil Service Hospital and National Cancer Hospital from August 2014-January 2016. The case record of all women diagnosed to have uterine cancer were retrieved and demographic characteristics, clinical presentations, histological type, treatment modalities and outcome were obtained and analyzed. Patients were followed up to five years and information regarding recurrence and mortality were obtained. Results: There were 30 uterine cancers cases during study period with age ranging from 33-72 years (mean 53.3years). One case was unmarried while rest 29 (96%) were married, with parity ranging from 0-11. Abnormal uterine and postmenopausal bleeding were the commonest presentations. Histopathologically, endometrial adenocarcinoma accounted for 25 cases (83%), uterine sarcoma four cases (13%) and malignant mixed mullerian tumour one case (4%). All the endometrial cancers were preoperatively diagnosed by endometrial biopsy whereas all cases of uterine sarcomas were reported as leiomyoma radiologically, had benign findings in endometrial biopsy and were only diagnosed post-operatively by histopathology. All cases were treated primarily with surgery. Twenty four patients (80%) received adjuvant therapy according to stage and grade of the disease. Clinical follow-up showed 18 (62%) cases were disease free; 11 (36.67%) developed recurrence, mortality occurred in 9 (31%), two are living with disease and one case is lost to follow up. Conclusions: Endometrial cancer can be usually diagnosed pre-operatively by endometrial biopsy, however, uterine sarcoma is often missed. Surgery is the main treatment modality of uterine cancers.